2002
DOI: 10.1002/cncr.10860
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine plus epirubicin in patients with advanced urothelial carcinoma who are not eligible for platinum‐based regimens

Abstract: BACKGROUNDThe objective of this study was to evaluate the efficacy and toxicity of gemcitabine plus epirubicin in previously untreated patients with advanced urothelial carcinoma who were not eligible for cisplatin‐based regimens.METHODSPatients with advanced urothelial carcinoma and at least one of the following characteristics were eligible: impaired renal function (creatinine clearance < 60 mL per minute), an Eastern Cooperative Oncology Group performance status (PS) ≥ 2, and age ≥ 75 years. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…infusion of a combination of GEM and anthracycline derivatives in advanced breast (37), pancreatic (38 -40), bladder (41,42), and non-small cell lung cancers (43) could be further improved by using the most effective in vitro scheme. Moreover, the synergistic interaction observed after 1-and 24-h exposures to drugs opens up interesting perspectives for infusional or systemic clinical treatments, and the scheme defined as the most active in this preclinical study has provided the basis for the rationale in an ongoing intravesical Phase I-II clinical protocol.…”
Section: Discussionmentioning
confidence: 99%
“…infusion of a combination of GEM and anthracycline derivatives in advanced breast (37), pancreatic (38 -40), bladder (41,42), and non-small cell lung cancers (43) could be further improved by using the most effective in vitro scheme. Moreover, the synergistic interaction observed after 1-and 24-h exposures to drugs opens up interesting perspectives for infusional or systemic clinical treatments, and the scheme defined as the most active in this preclinical study has provided the basis for the rationale in an ongoing intravesical Phase I-II clinical protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Other combinations with paclitaxel, oxaliplatin or epirubicin have shown some effectivity in small phase II trials [39][40][41].…”
Section: Systemic Therapy Of Muscle Invasive or Metastatic Bladder Camentioning
confidence: 99%
“…We used PS >1, creatinine clearance <50 ml/min and comorbidities precluding cisplatin administration as the criteria for unfitness, similar to those used in a recent multicenter EORTC study [27]. Age has also been previously used by us and others as a criterion for unfitness [12, 28]. Nevertheless, we subsequently showed that elderly patients can tolerate cisplatin-based combination chemotherapy equally well as their younger counterparts, provided that no comorbidities are present and the other 2 criteria of fitness are fulfilled [6].…”
Section: Discussionmentioning
confidence: 99%
“…In one study including 38 patients, a combination of epirubicin and gemcitabine was used [28]. Age was used as an additional criterion for unfitness for cisplatin.…”
Section: Discussionmentioning
confidence: 99%